Efficacy and safety of HSK21542 for pruritus management in hemodialysis patients: a multicenter, randomized, double-blind, placebo-controlled trial - Pan, Ming-Ming; Gao, Min; Zhou, Li; Xu, Yan; Yao, Li; Wu, Chao-Qing; Mei, Chang-Lin; Zhao, Zhan-Zheng; Sun, Dong; Guan, Tian-Jun; Chen, Qin-Kai; Shi, Ming; et al. (Frontiers in Pharmacology, 2025)
BackgroundChronic kidney disease-associated pruritus (CKD-aP) is a common and distressing symptom in hemodialysis patients. This Phase II trial evaluated the efficacy and safety of HSK21542, a selective kappa-opioid receptor agonist, in managing CKD-aP.MethodsAdult patients on hemodialysis with moderate to severe pruritus, were randomized 1:1:1 to placebo, or HSK21542 (0.3 μg/kg or 0.6 μg/kg) administered thrice weekly post-dialysis for 12 weeks. The primary endpoint was the change from baseline in the weekly mean of the worst itching intensity Numerical Rating Scale (WI-NRS) score at week 12. Secondary endpoints included quality-of-life assessments, safety evaluations, and pharmacokinetic properties.ResultsA total of 90 patients were enrolled. At week 12, mean changes in WI-NRS scores from baseline were −2.94 for the placebo group, −3.40 for the 0.3 μg/kg HSK21542 group, and −2.21 for the 0.6 μg/kg HSK21542 group. The percentages of patients who had a reduction of 3 points or above in their WI - NRS scores were 44.4% in the placebo group, 62.1% in the 0.3 μg/kg HSK21542 group, and 37.0% in the 0.6 μg/kg HSK21542 group. The 0.30 μg/kg HSK21542 group demonstrated more significant improvements in Skindex - 16 scores compared to the placebo. The 5-D Itch Scale scores also presented similar trends. Both the 0.3 μg/kg and 0.6 μg/kg doses of HSK21542 were well - tolerated, with no dose-dependent adverse effects.ConclusionThe 0.3 μg/kg dose of HSK21542 demonstrated superior efficacy and safety in reducing pruritus and improving quality of life in hemodialysis patients.